Journal des Économistes et des Études Humaines (De Gruyter, 1995)
The Journal des Économistes et des Études Humaines (JEEH) addresses economic issues in political theory, social dynamics, social science methodology, and philosophy. JEEH has an international audience and welcomes contributions written by scholars from around the world.